Positive electrode active material, lithium ion secondary battery, and method for producing positive electrode active material
By using lithium transition metal composite oxide with a stoichiometric oxygen amount of 1.9 or more, and firing raw materials under high oxygen partial pressure conditions, the problem of insufficient initial capacity of lithium-ion secondary batteries is solved, and higher initial capacity of battery and more stable battery performance is achieved.
Patent Information
- Application Number
- CN202411004642.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-24
- Filing Date
- 2024-07-25
- Publication Date
- 2025-04-25
AI Technical Summary
There is room for improvement in the initial capacity of lithium-ion secondary batteries.
The lithium transition metal composite oxide with a stoichiometric oxygen amount of 1.9 or more is used as the positive electrode active material, and the raw material is fired in an atmosphere with an oxygen partial pressure of 1.1 atm or more to improve the initial capacity of the battery.
By increasing the oxygen amount and optimizing the firing conditions, the initial capacity of the lithium-ion secondary battery is improved, the oxygen defects in the positive electrode active substance are reduced, the octahedral structure of the transition metal layer is stabilized, and the intercalation and deintercalation efficiency of lithium ions is improved.
Smart Images

Figure BDA0004962654540000091
Abstract
Description
Technical Field
[0001] The present disclosure relates to a positive electrode active material, a lithium ion secondary battery, and a method for producing the positive electrode active material. Background Art
[0002] Lithium transition metal composite oxides having a crystal structure in which transition metal layers and lithium layers are alternately arranged, and the transition metal layers include an octahedral structure composed of transition metal atoms and oxygen atoms, are widely used as positive electrode active materials for lithium ion secondary batteries.
[0003] The lithium transition metal composite oxide is produced by firing a raw material containing a transition metal and lithium in an atmosphere containing oxygen. The firing conditions of the raw material may affect the properties of the lithium transition metal composite oxide obtained after firing.
[0004] Japanese Patent Application Laid-Open No. 2018-193296 describes the following method for inhibiting the precipitation of lithium components on the surface of the obtained particles: the raw material of the lithium transition metal composite oxide is sintered at a temperature range of 450°C to 650°C under the condition that the oxygen partial pressure is 500 hPa to 1013.25 hPa (i.e., 0.5 atm to 1.0 atm). Summary of the invention
[0005] Lithium-ion secondary batteries using lithium-transition metal composite oxides as positive electrode active materials have room for improvement in initial capacity.
[0006] The present disclosure provides a positive electrode active material for a lithium ion secondary battery capable of obtaining improved initial capacity, a lithium ion secondary battery having a positive electrode containing the positive electrode active material, and a method for producing the positive electrode active material for a lithium ion secondary battery capable of obtaining improved initial capacity.
[0007] Means for solving the above-mentioned problems include the following embodiments.
[0008] <1> A positive electrode active material having a crystal structure in which transition metal layers and lithium layers are alternately arranged, and a stoichiometric oxygen content of 1.9 or more,
[0009] The transition metal layer includes at least one transition metal selected from the group consisting of nickel, cobalt, and manganese.
[0010] <2> A lithium ion secondary battery comprising: a positive electrode including the positive electrode active material according to <1>.
[0011] <3> A method for producing a positive electrode active material, comprising: firing a raw material of a positive electrode active material containing at least one transition metal selected from nickel, cobalt and manganese and lithium in an atmosphere containing oxygen,
[0012] The oxygen partial pressure of the above-mentioned atmosphere is 1.1 atm or more.
[0013] <4> The method for producing a positive electrode active material according to <3>, wherein:
[0014] The above oxygen partial pressure is 6.0 atm or less.
[0015] <5> The method for producing a positive electrode active material according to <3>, wherein:
[0016] The above oxygen partial pressure is 1.5atm to 3.0atm.
[0017] According to one embodiment of the present disclosure, a positive electrode active material for a lithium ion secondary battery having improved initial capacity, a lithium ion secondary battery having a positive electrode including the positive electrode active material, and a method for producing the positive electrode active material for a lithium ion secondary battery having improved initial capacity are provided. DETAILED DESCRIPTION
[0018] In the present disclosure, a numerical range expressed using “to” means a range including the numerical values described before and after “to” as the minimum value and the maximum value, respectively.
[0019] In the numerical ranges recorded in the present disclosure, the upper limit or lower limit recorded in a numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other sections. In the numerical ranges recorded in the present disclosure, the upper limit or lower limit recorded in a numerical range can be replaced by the values shown in the embodiments.
[0020] In the present disclosure, the term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.
[0021] In the present disclosure, a combination of two or more preferred aspects is a more preferred aspect.
[0022] In the present disclosure, when there are plural substances belonging to each component, the amount of each component means the total amount of the plural substances unless otherwise specified.
[0023] <Positive electrode active material>
[0024] The positive electrode active material disclosed in the present invention has a crystal structure in which transition metal layers and lithium layers are alternately arranged.
[0025] The stoichiometric oxygen content is 1.9 or more.
[0026] The transition metal layer includes at least one transition metal selected from the group consisting of nickel, cobalt, and manganese.
[0027] The positive electrode active material disclosed herein is a compound of a lithium transition metal composite oxide having a crystal structure in which transition metal layers and lithium layers are alternately arranged (also referred to as a layered stacking structure or an R-3m type crystal structure). The transition metal layer includes an octahedral structure composed of transition metal atoms and oxygen atoms.
[0028] In the present disclosure, the lithium-transition metal composite oxide refers to a composite oxide containing lithium and one or more transition metals.
[0029] As shown in the examples described below, a lithium ion secondary battery having a positive electrode including a positive electrode active material having a stoichiometric oxygen content of 1.9 or more exhibits a better initial capacity than a lithium ion secondary battery having a positive electrode including a positive electrode active material having a stoichiometric oxygen content of less than 1.9. The reasons are, for example, speculated as follows. However, the present disclosure is not limited by the following speculation.
[0030] Lithium transition metal composite oxide, which is a composite oxide of lithium and transition metal, is represented by the composition formula of LiMeO2 (Me represents transition metal). The valence of lithium is +1 and the valence of oxygen is -2, so the theoretical valence of the transition metal is +3.
[0031] However, the lithium transition metal composite oxide obtained by firing a raw material containing a transition metal and lithium actually contains oxygen defects generated during firing (that is, the stoichiometric oxygen amount is less than the theoretical 2.0), so Me 3+ and Me 2+ The mixture is present in the transition metal layer.
[0032] When Me 2+ When the proportion of the transition metal constituting the transition metal layer is large, the octahedral structure composed of transition metal atoms and oxygen atoms is distorted, and this distortion becomes a factor that hinders insertion and extraction of lithium ions between the transition metal layers.
[0033] The stoichiometric oxygen content of the positive electrode active material disclosed in the present invention is 1.9 or more. 2+ The proportion of the transition metal constituting the transition metal layer is small, and the octahedral structure composed of transition metal atoms and oxygen atoms becomes stable. As a result, the insertion and extraction of lithium ions between the transition metal layers becomes good, and the initial capacity of the battery is improved.
[0034] The positive electrode active material of the present disclosure is not particularly limited as long as it contains at least one selected from nickel, cobalt, and manganese as a transition metal.
[0035] In one embodiment, the positive electrode active material preferably contains at least nickel as a transition metal, more preferably contains nickel and at least one selected from cobalt and manganese, and further preferably contains nickel, cobalt and manganese (NCM, nickel cobalt manganese oxide).
[0036] NCM may contain Ni at a high ratio (for example, 70 mol % or more of the entire transition metal).
[0037] The molar ratio of Ni, Co, and Mn contained in the NCM may be, for example, a molar ratio of Ni to Co (Ni:Co) selected from the range of 1:0.1 to 1:1, or a molar ratio of Ni to Mn (Ni:Mn) selected from the range of 1:0.1 to 1:1.
[0038] The molar ratio of Ni to Co (Ni:Co) may be selected from the range of 1:0.1 to 1:0.5, 1:0.1 to 1:0.3, or 1:0.1 to 1:0.2.
[0039] The molar ratio of Ni to Mn (Ni:Mn) may be selected from the range of 1:0.1 to 1:0.5, 1:0.1 to 1:0.3, or 1:0.1 to 1:0.2.
[0040] The positive electrode active material disclosed herein may be composed only of lithium, oxygen and a transition metal selected from Ni, Co and Mn, or may contain elements other than these (hereinafter referred to as other elements). Other elements include Al, B, Mg, Ti, V, Cr, Fe, Cu, Zn, Ga, Sr, Zr, Nb, In, Sn, Ta, W, La, B, Ru, Cd, Ag, Y, Sc, As, Sb, Pt, Au, Si, etc.
[0041] When the positive electrode active material of the present disclosure contains other elements, the ratio thereof may be 10 mol % or less, 5 mol % or less, or 1 mol % or less of the entire positive electrode active material.
[0042] When the positive electrode active material of the present disclosure contains other elements, the ratio thereof may be 0.001 mol % or more, 0.01 mol % or more, or 0.1 mol % or more of the entire positive electrode active material.
[0043] The stoichiometric oxygen amount of the positive electrode active material of the present disclosure is 1.9 or more.
[0044] From the viewpoint of the initial capacity of the battery, the stoichiometric oxygen amount of the positive electrode active material is preferably 1.92 or more, more preferably 1.94 or more, and even more preferably 1.96 or more.
[0045] The stoichiometric oxygen content of the positive electrode active material may be 2.0, less than 2.0, 1.99 or less, or 1.985 or less.
[0046] The stoichiometric oxygen content of the positive electrode active material can be adjusted by, for example, the conditions when firing the raw material of the positive electrode active material. Specific examples of the conditions when firing the raw material of the positive electrode active material include the oxygen partial pressure of the firing atmosphere.
[0047] In the present disclosure, the stoichiometric oxygen amount of the positive electrode active material is measured by iodine titration.
[0048] The positive electrode active material may be in a particle form. The volume average particle size of the particle-shaped positive electrode active material is not particularly limited, and may be selected, for example, from a range of 5 μm to 30 μm. When the positive electrode active material is a secondary particle that is an aggregate of a plurality of primary particles, the above volume average particle size is the volume average particle size of the secondary particles.
[0049] The volume average particle size of the positive electrode active material particles is not particularly limited, and can be selected from the range of 5 μm to 30 μm, for example.
[0050] In the present disclosure, the volume average particle size of particles is a particle size (D50) when the cumulative volume is 50% in a volume-based particle size distribution. The volume-based particle size distribution is obtained by, for example, a laser diffraction / scattering method.
[0051] <Lithium-ion secondary battery>
[0052] The lithium ion secondary battery of the present disclosure includes a positive electrode including the positive electrode active material described above.
[0053] The positive electrode includes, for example, a current collector and a positive electrode layer disposed on the current collector, and the positive electrode layer contains the positive electrode active material of the present disclosure.
[0054] The positive electrode layer may be disposed on one surface or both surfaces of the current collector.
[0055] Examples of the material of the current collector constituting the positive electrode include aluminum, aluminum alloys, nickel, titanium, stainless steel, etc. Examples of the shape of the current collector include foil, mesh, and the like.
[0056] The positive electrode layer is disposed on the current collector by, for example, coating a slurry of positive electrode material on one or both sides of the current collector. A pressurization treatment may be performed to adjust the density of the positive electrode layer as required. The thickness of the positive electrode layer is not particularly limited, and may be selected from a range of, for example, 10 μm to 100 μm.
[0057] The positive electrode material may be in the form of a mixture containing components other than the positive electrode active material, such as a conductive auxiliary agent and a binder. If necessary, a solvent may be added to the mixture to adjust the viscosity of the mixture.
[0058] Specific examples of the conductive auxiliary agent include carbon materials such as carbon black (acetylene black, thermal black, furnace black, etc.), carbon nanotubes, and graphite.
[0059] The conductive material contained in the positive electrode material may be one kind alone or two or more kinds thereof.
[0060] Specific examples of the binder include polyvinylidene fluoride (PVDF), polyethylene, polypropylene, polyethylene terephthalate, cellulose, nitrocellulose, carboxymethyl cellulose, polyethylene oxide, polyepichlorohydrin, polyacrylonitrile, styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), polyacrylate, and polymethacrylate.
[0061] The binder contained in the positive electrode material may be one kind alone or two or more kinds thereof.
[0062] The lithium ion secondary battery of the present disclosure includes, for example, a positive electrode, a negative electrode, and an electrolyte.
[0063] The negative electrode includes, for example, a current collector and a negative electrode layer disposed on the current collector and containing a negative electrode active material.
[0064] Examples of the negative electrode active material include carbon materials such as graphite, hard carbon, soft carbon, and activated carbon, silicon, metallic lithium, lithium alloys, and lithium titanate (LTO).
[0065] Examples of the material of the current collector constituting the negative electrode include copper, copper alloys, nickel, titanium, stainless steel, etc. Examples of the shape of the current collector of the negative electrode include foil, mesh, and the like.
[0066] The electrolyte may be liquid or solid. As the liquid electrolyte (electrolyte), a liquid electrolyte (electrolyte solution) obtained by dissolving a known electrolyte such as LiPF6 in an organic solvent may be used without particular limitation.
[0067] As the organic solvent, specific examples include cyclic or chain carbonates such as ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). The solvent may be a mixture of two or more solvents, or a mixture containing cyclic carbonates and chain carbonates.
[0068] The solvent may contain additives such as vinylene carbonate (VC).
[0069] As the solid electrolyte, a known solid electrolyte such as a sulfide solid electrolyte, an oxide solid electrolyte, or a halide solid electrolyte can be used without particular limitation.
[0070] The lithium ion secondary battery may include a separator disposed between the positive electrode and the negative electrode. Examples of the separator include nonwoven fabrics, fabrics, and microporous films mainly composed of polyolefins such as polyethylene and polypropylene.
[0071] <Method for producing positive electrode active material>
[0072] The method for producing a positive electrode active material disclosed herein comprises: a step of firing a raw material of a positive electrode active material containing at least one transition metal selected from nickel, cobalt and manganese and lithium in an atmosphere containing oxygen (hereinafter also referred to as a firing step);
[0073] The oxygen partial pressure of the above-mentioned atmosphere is 1.1 atm or more.
[0074] As shown in the embodiments described below, a lithium ion secondary battery having a positive electrode including a positive electrode active material obtained by performing a firing process in an atmosphere with an oxygen partial pressure of 1.1 atm or more shows a better initial capacity than a lithium ion secondary battery having a positive electrode including a positive electrode active material obtained by performing a firing process in an atmosphere with an oxygen partial pressure of less than 1.1 atm. The reasons are, for example, speculated as follows. However, the present disclosure is not limited by the following speculation.
[0075] A battery using a positive electrode active material obtained by subjecting the firing step to an atmosphere with an oxygen partial pressure of 1.1 atm or more has a stoichiometric oxygen content greater than that of a positive electrode active material obtained by subjecting the firing step to an atmosphere with an oxygen partial pressure of less than 1.1 atm.
[0076] That is, by carrying out the firing process in an atmosphere with an oxygen partial pressure of 1.1 atm or more, the amount of oxygen defects generated during firing is reduced, and the octahedral structure composed of transition metal atoms and oxygen atoms constituting the transition metal layer becomes stable. As a result, the insertion and extraction of lithium ions between the transition metal layers become good, and the initial capacity of the battery is improved.
[0077] The oxygen partial pressure of the atmosphere in which the firing step is performed is not particularly limited as long as it is 1.1 atm or more, but as shown in the examples described later, the stoichiometric amount of oxygen tends to increase with increasing oxygen partial pressure. Therefore, the oxygen partial pressure of the atmosphere in which the firing step is performed may be 1.5 atm or more, 2.0 atm or more, or 2.5 atm or more.
[0078] The upper limit of the oxygen partial pressure of the atmosphere in which the firing step is performed is not particularly limited, but as shown in the examples described later, the increase in the stoichiometric oxygen amount tends to decrease as the oxygen partial pressure increases.
[0079] Therefore, the oxygen partial pressure of the atmosphere in which the firing step is performed may be 6.0 atm or less, 5.0 atm or less, or 3.0 atm or less.
[0080] From the viewpoint of balancing the increase in the stoichiometric oxygen amount of the positive electrode active material and economic efficiency, the oxygen partial pressure of the atmosphere in which the firing step is performed may be within a range of 1.5 atm to 3.0 atm.
[0081] The oxygen partial pressure of the atmosphere in which the firing step is performed may be constant from the start to the end of the firing step, or may vary. The firing step may or may not include a period in which the oxygen partial pressure is less than 1.1 atm.
[0082] The oxygen partial pressure of the atmosphere for firing the raw material of the positive electrode active material can be adjusted by, for example, operating a valve of an apparatus used for firing.
[0083] The oxygen content in the atmosphere for performing the firing step can be selected from the range of 60 volume % to 100 volume %, for example.
[0084] The temperature when the firing step is performed is not particularly limited and can be selected from known firing conditions. The firing temperature can be selected from a range of 600°C to 850°C, for example.
[0085] From the viewpoint of obtaining a positive electrode active material having a sufficiently large stoichiometric oxygen amount under appropriate sintering conditions, the sintering temperature is preferably lower than 750° C., more preferably 730° C. or lower, and even more preferably 720° C. or lower.
[0086] The temperature during the firing step may be constant from the start to the end of the firing step, or may be variable.
[0087] The raw material of the positive electrode active material fired in the firing step is not particularly limited and can be selected from known raw materials.
[0088] In one embodiment, the raw material of the positive electrode active material may be a mixture containing a compound (hydroxide, carbonate, etc.) containing at least one selected from nickel, cobalt and manganese and a compound (hydroxide, carbonate, etc.) containing lithium.
[0089] The positive electrode active material produced by the method of the present disclosure may be the positive electrode active material of the present disclosure described above. That is, the details and preferred embodiments of the positive electrode active material produced by the method of the present disclosure may be the same as the details and preferred embodiments of the positive electrode active material of the present disclosure described above.
[0090] The present disclosure is further described in detail below through examples, but the present disclosure is not limited to these examples.
[0091] <Preparation of positive electrode active material>
[0092] NiSO4, CoSO4 and MnSO4 were dissolved in ion exchange water to obtain a raw material solution having a concentration of 30 mass %. The molar ratios of Ni, Co and Mn in the raw material solution were the values shown in Table 1.
[0093] An NH3 aqueous solution was added to the reaction vessel, and nitrogen substitution was performed while stirring. Next, NaOH was added to the reaction vessel to adjust the aqueous solution to be alkaline.
[0094] While controlling the pH in the reaction container to be constant, the raw material solution and NH3 are added dropwise to precipitate the hydroxides of Ni, Co and Mn. The obtained precipitate is taken out by filtration and dispersed in ion exchange water. The hydroxide dispersed in the ion exchange water is filtered and dried at 120°C for 16 hours to remove moisture, thereby obtaining a transition metal hydroxide as a precursor of the positive electrode active material.
[0095] Lithium hydroxide was added to the obtained precursor and mixed to obtain a raw material of a positive electrode active material. The amount of lithium hydroxide was adjusted to 1 mol per 1 mol of the total of transition metals (Ni, Co, and Mn) in the precursor.
[0096] The raw material of the positive electrode active material was fired at 700° C. for 10 hours in a pressure firing furnace into which oxygen was introduced to obtain positive electrode active materials of Comparative Example 1 and Examples 1 to 5. The firing was performed while adjusting the oxygen partial pressure in the firing furnace to the value shown in Table 1.
[0097] The stoichiometric oxygen content of the obtained positive electrode active material was measured by iodine titration.
[0098] <Evaluation of initial battery capacity>
[0099] The positive electrode active material (88 parts by mass), acetylene black (10 parts by mass) as a conductive material and polyvinylidene fluoride (2 parts by mass) as a binder were mixed, and the viscosity was adjusted with a solvent to obtain a positive electrode composite material. The positive electrode composite material was coated on an aluminum foil and dried at 80°C for 5 minutes to obtain a positive electrode.
[0100] A laminated evaluation cell was prepared using an electrode body in which the obtained positive electrode, separator (polyethylene microporous film) and negative electrode containing graphite as an active material were stacked in sequence, and an electrolyte. As the electrolyte, a mixed solvent of ethylene carbonate (EC) dissolved with LiPF6 (concentration: 1M), DMC and EMC (the volume ratio of EC / DMC / EMC was 3 / 4 / 3) was used.
[0101] For the evaluation battery, the discharge capacity during CCCV charging (1.5 to 4.1 V) at a current value of 0.1 C was measured and used as the initial capacity. The initial capacities of Examples 1 to 5 indexed using the initial capacity measured using the positive electrode active material of Comparative Example 1 as a reference value (100) are shown in Table 1.
[0102] Table 1
[0103]
[0104] As shown in Table 1, the initial capacity of the battery obtained by using the positive electrode active materials of Examples 1 to 5 having a stoichiometric oxygen content of 1.9 or more is greater than the initial capacity of the battery obtained by using the positive electrode active material of Comparative Example 1 having a stoichiometric oxygen content of less than 1.9. The above results show that the stoichiometric oxygen content of the positive electrode active material is a factor related to the initial capacity of the battery.
[0105] Furthermore, the stoichiometric oxygen amount of the positive electrode active materials of Examples 1 to 5 obtained by setting the oxygen partial pressure of the atmosphere of the raw material of the positive electrode active material to 1.1 atm or more is greater than the stoichiometric oxygen amount of the positive electrode active material of Comparative Example 1 obtained by setting the oxygen partial pressure of the atmosphere of the raw material of the positive electrode active material to 1.0 atm. The above results show that by setting the oxygen partial pressure of the atmosphere of the raw material of the positive electrode active material to 1.1 atm or more, the oxygen defects in the positive electrode active material are reduced and the stoichiometric oxygen amount of the positive electrode active material is increased.
Claims
1. A positive electrode active material having a crystal structure in which transition metal layers and lithium layers are alternately arranged, and the stoichiometric oxygen content is 1.9 or more, The transition metal layer includes at least one transition metal selected from the group consisting of nickel, cobalt, and manganese. 2 . A lithium ion secondary battery comprising: a positive electrode comprising the positive electrode active material according to claim 1 .
3. A method for producing a positive electrode active material, comprising: A step of firing a raw material of a positive electrode active material containing at least one transition metal selected from nickel, cobalt and manganese and lithium in an atmosphere containing oxygen, The oxygen partial pressure of the atmosphere is greater than 1.1 atm.
4. The method for producing a positive electrode active material according to claim 3, wherein: The oxygen partial pressure is below 6.0 atm.
5. The method for producing a positive electrode active material according to claim 3, wherein: The oxygen partial pressure is 1.5 atm to 3.0 atm.
Citation Information
Patent Citations
Production method of lithium nickel composite oxide
JP2018193296A